Correction: Interface structure, precursor rheology and dielectric properties of BaTiO3/PVDF–hfp nanocomposite films prepared from colloidal perovskite nanoparticles. Issue 73 (27th September 2017) - Hao, Y. N.; Bi, K.; O'Brien, S.; Wang, X. H.; Lombardi, J.; Pearsall, F.; Li, W. L.; Lei, M.; Wu, Y.; Li, L. T.
Abstract : Correction for 'Interface structure, precursor rheology and dielectric properties of BaTiO3 /PVDF–hfp nanocomposite films prepared from colloidal perovskite nanoparticles' by Y. N. Hao et al., RSC Adv., 2017, 7, 32886–32892.